Variation in the fitness impact of translationally optimal codons among animals - Bénitière, Florian; Lefébure, Tristan; Duret, Laurent (Genome Research, 2025)
Early studies in invertebrate model organisms (fruit flies, nematodes) showed that their synonymous codon usage is under selective pressure to optimize translation efficiency in highly expressed genes (a process called translational selection). In contrast, mammals show little evidence of selection for translationally optimal codons. To understand this difference, we examined the use of synonymous codons in 223 metazoan species, covering a wide range of animal clades. For each species, we predicted the set of optimal codons based on the pool of tRNA genes present in its genome, and we analyzed how the frequency of optimal codons correlates with gene expression to quantify the intensity of translational selection (S). We observed that few metazoans show clear signs of translational selection. As predicted by the nearly neutral theory, the highest values of S are observed in species with large effective population sizes (Ne). Overall, however, Ne appears to be a poor predictor of the intensity of translational selection, suggesting important differences in the fitness effect of synonymous codon usage across taxa. We propose that the few animal taxa that are clearly affected by translational selection correspond to organisms with strong constraints for a very rapid growth rate.